Are Pedagogical Students More Creative than Students of Non-Pedagogical Programs? - Zemljak, Dejan; Ploj Virtič, Mateja (Revija za elementarno izobraževanje, 2022)
The study aims to explore whether there are significant differences in self-assessed creativity between pedagogical and non-pedagogical students, the potential connection between creativity and pedagogical or non-pedagogical study orientation, whether the pedagogical or non-pedagogical orientation of studies influences creativity, and additionally whether there are significant differences in self-assessed creativity between the genders, related to the results of creativity self-assessment. The results showed no statistically significant differences in creativity between students according to gender or according to whether they were pedagogical or non-pedagogical students. We can conclude that the expression of creativity is likely to be influenced by many other factors.
Keywords: creativity, gender, pedagogical and non-pedagogical orientation of study, university students